THE THORACIC OUTLET SYNDROME AND A PHYSIOTHERAPY INTERVENTION (Fiep Bulletin - online, 2014)
The thoracic outlet syndrome (TOS) is a generic term to define symptoms and signs of vascular or nervous compression in some area between the neck and the armpit. The clinical aspects can be characterized by vascular or nervous alterations, varying in kind and intensity of pain, with an imprecise location followed by weakness and paresthesia. When a compression of the superior lace of brachial plexus occurs, pain in the lateral area of the neck, head and rhomboids region and suprascapular may appear. With the re-evaluation, the aims of the treatment were to reduce the pain, the nervous compression, regaining the movement amplitude and normality of the strengthened effective muscles of the patient's scapular waist. Thus, subject was used for this research, L.F.C. aged 39, male, with a TOS clinical diagnosis. He was evaluated at Physiotherapy Clinical School of UNIGUAÇU College, located in União da Vitória, State of Paraná, South of Brazil, after medical guiding with conservative treatment indication. The treatment based on manual therapies and muscular strengthen contributed for the reduction of the threshold of pain, favoring the positive prognostic to the physiotherapeutic treatment.
Keywords: thoracic outlet; physiotherapy; nervous compression